Antimicrobial and antioxidant activities of a new metabolite from Quercus incana. Issue 16 (18th August 2017) - Gul, Farah; Khan, Khalid Mohammed; Adhikari, Achyut; Zafar, Salman; Akram, Muhammad; Khan, Haroon; Saeed, Muhammad
Abstract: Phytochemical investigations of Quercus incana led to the isolation of a new catechin derivative quercuschin (1 ), along with six known compounds: quercetin(2 ), methyl gallate (3 ), gallic acid (4 ), betulinic acid (5 ), ( Z )-9-octadecenoic acid methyl ester (6 ) and β-sitosterol glucoside (7 ) from the ethyl acetate fraction of methanolic extract of the bark. Compound1 was screened for its antibacterial, antifungal and antioxidant potential. Antibacterial and antifungal activities of the compound were tested against different bacterial and fungal strains, employing the agar well diffusion methods. The antibacterial activity was the highest against Streptococcus pyogenes with 80.0% inhibition, while the antifungal activity of the compound was the highest against Candida glabrata with 80.5% inhibition. The results of the antioxidant activity indicated that the compound exhibited antioxidant activity comparable to that of standard, butylated hydroxyanisole (51.2 μg/10 μl versus 45.9 μg/10 μl). Abstract :